Efficacy and safety of topical isobutylamido thiazolyl resorcinol (Thiamidol) vs. 4% hydroquinone cream for facial melasma: an evaluator-blinded, randomized controlled trial - Lima, P. B. [UNESP]; Dias, J. A.F. [UNESP]; Cassiano, D. P.; Esposito, A. C.C. [UNESP]; Miot, L. D.B. [UNESP]; Bagatin, E.; Miot, H. A. [UNESP] (Wiley, 2021)
Background: Melasma can be refractory to treatment, and relapses are frequent. Thiamidol is a new potent tyrosinase inhibitor that has been found effective as a cosmeceutical for the depigmenting of melasma. Objective: This study compared the efficacy and tolerability of topical 0.2% Thiamidol vs. 4% hydroquinone for facial melasma. Methods: Fifty women with facial melasma participated in a randomized, evaluator-blinded, controlled study from September through November 2020. Patients were randomly assigned to apply a double layer of 0.2% Thiamidol twice a day or 4% hydroquinone cream at bedtime, for 90 days. Both groups received tinted sunscreen (sun protection factor 60, PPD 20). The primary outcome was the change from the baseline Modified Melasma Area Seve:rity Index (mMASI) score. Secondary outcomes were improvements in the patients’ quality of life [Melasma Quality of Life Index (MELASQoL)], colourimetry, and Global Aesthetic Improvement Scale (GAIS) evaluation. Results: One participant, from the hydroquinone group, did not complete the study (unrelated to adverse effects). The mean (SD) age of the participants was 43 (6) years, and 86% were phototypes III–IV. Both groups exhibited a reduction in mMASI, MELASQoL, and colour contrast scores (P < 0.01). The mean [95% confidence interval (CI 95%)] reductions of the mMASI scores were 43% (35–50%) for Thiamidol and 33% (23–42%) for hydroquinone. There was no difference between the groups in the reductions in mMASI, MELASQoL, colourimetric contrast and GAIS scores (P ≥ 0.09). The GAIS analysis resulted in an improvement of 84% (CI: 95% 67–97%) for participants in the Thiamidol group and 74% (CI: 95% 61–93%) for those in the hydroquinone group. There were only mild adverse effects in the Thiamidol group, but allergic contact dermatitis was evidenced in two (8%) participants. Conclusion: The melasma improvement achieved using 0.2% Thiamidol did not differ from that of 4% hydroquinone cream. Thiamidol can be considered a suitable option for melasma patients with poor tolerability or treatment failure with hydroquinone.